Rozwój gospodarczy polskich regionów na podstawie analizy shift-share w latach 1999-2004 - Łaźniewska, Ewa; Górecki, Tomasz (Economic Development of Polish Regions on the Basis of the Shift-share Analysis in the Period 1999-2004, 2008)
The authors of the paper intend to present in a synthetic way different models of the shift-share method which has not found any reflection in the Polish literature, but is a very popular method applied by economists world-wide. The shift-share analysis was conducted based on three models: the classical shift-share model, the Rigby-Anderson model and the Haynes-Dinc model. The whole of the empirical research is based on the data available at NUTS II level, i.e. voivodships. From the point of view of economies of countries in transition, especially interesting is the fact that the results of analyses often do not correspond to similar observations in countries which have stable market economies. Especially noticeable are adverse tendencies to strengthen the structures based on agricultural economy. All these considerations are closed by the results of the analysis of the value and dynamics of the location quotient, which makes it possible to classify the Polish regions into one of the four groups. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 187-196